WEE1 Inhibition by AZD1775 Augments Colorectal Cancer Cells Susceptibility to VE-822-induced DNA Damage and Apoptosis - Mihanfar, Ainaz; Asghari, Faezeh; Majidinia, Maryam (Drug Research, 2025)
WEE1 is a key tyrosine kinase involved in the cell cycle regulation with potent anticancer effects in various cancer types including colorectal cancer. Recent studies have focused on the potential of combinational inhibition of Ataxia Telangiectasia and Rad-3-related protein (ATR) and WEE1 in increasing apoptosis in cancer cells. Therefore, this study investigates the effects of inhibiting WEE1, by employing AZD1775, on colorectal cancer cellsʼ susceptibility to VE-822-induced DNA damage and apoptosis.SW-480 and HT-29 cells were treated with AZD1775 and VE-822, alone and in combination. MTT assay was used to assess cell proliferation and viability. The mRNA levels of ATR, checkpoint kinase 1 (CHK1), WEE1, ribonucleotide reductase (RR) catalytic subunit M1 (RRM1) and RRM2 were measured by qRT-PCR. Cellular γ-(H2A histone family member X) H2AX levels were measured by Western blot. Analyses were conducted using ELISA to assess 8-Oxo-2ʼ-deoxyguanosine (8-oxo-dG) levels. Lactate dehydrogenase (LDH) and ELISA death assays were used to assess apoptosis.The SW-480 and HT-29 cells have low proliferation rate when treated with VE-822 and AZD1775. The IC50 value for VE-822 was 1.3 μM and 1.6 μM in SW480 and HT-29, respectively. Also, this value for AZD1775 in SW480 was 140 nM and in HT-29 was 185 nM. The expression levels of ATR, CHK1, WEE1, RRM1, and RRM2 were significantly downregulated in both cell lines treated with combination of VE-822 and AZD1775 (P<0.05). DNA damage markers, including γ-H2AX and 8-oxo-dG were upregulated in these cells. Simultaneous treatment with VE-822 and AZD177 increased apoptosis capacity of both cell lines.The inhibition of WEE1 via AZD1775 potentiated the anticancer effects of ATR inhibitor, VE-822, in combating colorectal cancer via targeting DNA damage.
Keywords: apoptosis; cancer; anticancer drugs